The Concept of Data Privacy Law and its Application to the Internet - B. Svantesson, Dan Jerker (2015)
In a society where data is the lifeblood, data privacy will inevitably play a central role. In this article, I will examine in some detail the concept of data privacy law and how it applies to Internet conduct. This is a dauntingly large topic and as a consequence, the selection of issues discussed has had to be somewhat eclectic.